The Effect of Risk Management onthe Role of Manager and Their Implications on Performance - Hendiarto, R. Susanto; Pasaribu, Silvia Rachel (STKIP Yapis Dompu, 2023)
The current problem is that performance is still far from expectations, while the role of managers has not been encouraging, this is presumably because digital mastery in the business environment is still a concern. This study aims to determine the effect of risk management on the role of managers and their implications for performance, a case study on the West Java Chamber of Commerce and Industry fostered in Bandung. The research method applied is in the form of a descriptive analytical survey method, while the sample used is 50 respondents. The variables studied from each respondent are risk management, the role of managers, and performance. The type of data collected is primary data. The results showed that risk management had no and no significant effect on the manager's role, the manager's role had no effect and was significant on performance, risk management had no and no significant effect on performance. The implication is that risk management needs to be applied programmatically and massively. The object of this research is the sample of respondents used is still limited to the business assisted by the West Java Chamber of Commerce in Bandung, therefore further research needs to be carried out based on more varied sampling with a longer duration, so that generalizable results are obtained.